Sustainable Operations Management Practices and Competitive Advantage of Manufacturing Firms in Kenya - Rehema Swalehe; Stephen Odock; Gituro Wainaina (European Scientific Journal, ESJ, 2020)
Sustainable Operations Management refers to strategies, actions, and techniques that support operational policies in achieving environmental and economic objectives. This paper focuses on examining the effect of Sustainable Operations Management Practices on the competitive advantage of manufacturing firms in Kenya. Despite the importance of green innovation to green issues and success in the business, a review of studies revealed limited information in connection to the strategic role played by sustainable operations technologies. This paper adopted a positivist philosophy to the development of knowledge and used a cross-sectional survey research design. The population sample consisted of 903 manufacturing firms registered with the Kenya Association of Manufacturers. A sample size of 277 was calculated using Slovin’s formula, and a sample of 300 was used to cater for non-response. Primary data was collected. Validity and reliability were also tested and finally, data was analyzed using covariance-based Structural Equation Modeling (SEM). The results showed that Sustainable Operations Management Practices have a significant influence on a firm’s competitive advantage. The main conclusion was that Sustainable Operations Management Practices lead to minimized operating costs, enhanced satisfaction of employees, and environmental improvement leading to competitive advantage. The paper recommends the implementation of Sustainable Operations Management Practices by manufacturing firms since it comes with some advantages. The findings of the paper are relevant to the advancement of environmental policy and practices. It also adds knowledge by providing theoretical underpinning, conceptual and methodological references.